Quality seeds, improved varieties: The economics of crop genetic improvement and farmer uptake - Kramer, Berber; Spielman, David J. (International Food Policy Research Institute, 2025)
Crop genetic improvement has long been a cornerstone of global efforts to enhance agricultural productivity, improve food security, and foster economic development. This chapter explores evidence on the contribution of crop improvement to productivity, nutrition, environment, and poverty outcomes, before assessing evolutions in policy research and important areas for future research.